Effect of different doses of oxytocin on cardiac electrophysiology and arrhythmias induced by ischemia - Fariba Houshmand; Mahdieh Faghihi; Alireza Imani; Soleiman Kheiri (Wolters Kluwer Medknow Publications, 2017)
The onset of acute myocardial ischemia (MI) is accompanied by a rapid increase in electrical instability and often fatal ventricular arrhythmias. This study investigated that whether oxytocin (OT) can modulate ischemia-induced arrhythmias and considered relationships between the severity of arrhythmia and the electrocardiogram parameters during ischemia. OT (0.0001-1 μg) was administrated intraperitoneally 30 min before ischemia. To examine receptor involved, a selective OT-receptor antagonist, atosiban (ATO), was infused 10 min before OT. OT caused a significant and biphasic dose-dependent reduction in ectopic heart activity and arrhythmia score. OT doses that reduced ventricular arrhythmia elicited significant increase in QT interval. OT attenuated the electrophysiological changes associated with MI and there was significant direct relationship between QRS duration and arrhythmia score. ATO treatment reduced beneficial effects of OT on arrhythmogenesis. Nevertheless, ATO failed to alter OT effects on premature ventricular contractions. We assume that the ability of OT to modulate the electrical activity of the heart may play an important role in the antiarrhythmic actions of OT.